2022
DOI: 10.21037/tau-21-914
|View full text |Cite
|
Sign up to set email alerts
|

TLN2 functions as a tumor suppressor in clear cell renal cell carcinoma via inactivation of the Wnt/β-catenin signaling pathway

Abstract: Background: Clear cell renal cell carcinoma (ccRCC) is one of the most prevalent malignancies worldwide, but there is lack of reliable clinical diagnostic biomarkers. We explored the clinical value and functions of Talin 2 (TLN2) in the progression of ccRCC.Methods: A bioinformatic analysis was performed to determine the clinical value of TLN2 in ccRCC.TLN2 expression was evaluated by immunohistochemistry (IHC), real-time quantitative polymerase chain reaction (RT-qPCR) and western blot in ccRCC tissues and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Cai et al. found that low levels of TLN2 notably correlated with shorter survival rates and tumor aggressiveness in patients with ccRCC, and TLN2 strongly correlated with ccRCC proliferation, migration, and invasion via regulation of the Wnt/β‐catenin pathway 54 . However, the regulatory mechanism of their interaction in ccRCC has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al. found that low levels of TLN2 notably correlated with shorter survival rates and tumor aggressiveness in patients with ccRCC, and TLN2 strongly correlated with ccRCC proliferation, migration, and invasion via regulation of the Wnt/β‐catenin pathway 54 . However, the regulatory mechanism of their interaction in ccRCC has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Both talin1 and talin2 correlate with the malignancy potential of the human hepatocellular carcinoma MHCC-97 L cells [ 57 ]. Conversely, talin2 is downregulated in clear cell renal cell carcinoma (ccRCC) tissues and cells, and its overexpression in ccRCC cell lines inhibits cell growth and metastasis [ 58 ]. It remains to be discovered which factors influence the role of talin2 in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, Xu et al (2022) demonstrated that the upregulation of SDHA resulted in a significant suppression of the Wnt/ β -catenin signal pathway by decreasing the β -catenin expression in ccRCC. Moreover, the activator of Wnt/ β -catenin signal pathway can attenuate the inhibition on the malignancy of ccRCC cells caused by TLN2 overexpression ( Cai et al, 2022 ). And SOX17 displayed the similar function as TLN2 ( Wang et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%